KORELASI FATIGUE DENGAN DEMOGRAFI, SKALA PERFORMA DAN INDEK MASA TUBUH PADA PASIEN KANKER DEWASA - Achmad Fauji; Sara Tania; Ade Suryani; Retno Purwanti; Susan Yulia (Jurnal Ilmu Keperawatan Medikal Bedah, 2022)
In Indonesia, the association between fatigue and predictors of fatigue has nearly never been studied, particularly in adult cancer patients. This research is part of a larger research project to predict the prevalence of fatigue in adult people with cancer. The objective of this study was to determine the relationship between fatigue, respondent characteristics, and the performance scale among adult cancer patients in one-day care units. This study is a quantitative correlation investigation using a cross-sectional design with correlation and t-tests. Sixty-seven participants were selected from the medical records of adult cancer patients who met the criteria. Research findings indicated that there was no correlation between age, gender, type of cancer, ECOG (Eastern Cooperative Oncology Group) Performance Scale, and body mass index on the incidence of fatigue in adult cancer patients (Pvalue = 0.684; 0.977; 0.38; 0.224; 0.284), although there was a significant correlation between a previous fatigue and the occurrence of recent fatigue (Pvalue = 0.000). This study may be utilized as a basis for future studies on adult cancer patients experiencing fatigue in hospital settings.